1997
DOI: 10.1111/j.1365-2494.1997.tb02355.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of length of grazing session, rumen fill and starvation time before grazing on dry‐matter intake, ingestive behaviour and dry‐matter rumen pool sizes of grazing lactating dairy cows

Abstract: The effects of the length of allowed grazing time (Experiment 1) and length of starvation period before grazing (Experiment 2) on dry-matter (DM) intake, ingestive behaviour and changes in DM rumen pool sizes during the first grazing bout were investigated in lactating Holstein-Friesian dairy cows. In Experiment 1, four lengths of allowed grazing time (1, 1·75, 2·50 and 3·25 h) after overnight starvation were compared. Increasing the length of the allowed grazing time significantly increased DM intake (P < 0·0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
20
2
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 30 publications
(51 reference statements)
8
20
2
3
Order By: Relevance
“…The greater proportion of cows grazing at 6, 12 and 19 h after entering the pasture allocation also confirms the likelihood of cows to perform grazing in bouts, separated by periods of ruminating or idling (Gibb et al, 1997). Previous studies found that effective grazing time was related to, but not proportional to, total available time (Chilibroste et al, 1997). In addition, despite certain levels of observed grazing synchrony having been previously described for lactating cows (Rook and Huckle, 1995) and non-lactating ewes (Rook and Penning, 1991), in this study cows entered the pasture allocation at different times, after different periods of fasting, and could exit at different times owing to voluntary cow traffic.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The greater proportion of cows grazing at 6, 12 and 19 h after entering the pasture allocation also confirms the likelihood of cows to perform grazing in bouts, separated by periods of ruminating or idling (Gibb et al, 1997). Previous studies found that effective grazing time was related to, but not proportional to, total available time (Chilibroste et al, 1997). In addition, despite certain levels of observed grazing synchrony having been previously described for lactating cows (Rook and Huckle, 1995) and non-lactating ewes (Rook and Penning, 1991), in this study cows entered the pasture allocation at different times, after different periods of fasting, and could exit at different times owing to voluntary cow traffic.…”
Section: Discussionsupporting
confidence: 56%
“…Studies conducted in conventional pasture-based systems have analyzed the impact of supplementation (Phillips and Leaver, 1986;Sheahan et al, 2011), frequency of pasture allocation (Dalley et al, 2001;Granzin, 2003), pasture height (Gibb et al, 1997) and pasture allowance (Chilibroste et al, 2012), together with available grazing time (Gregorini et al, 2009;Kennedy et al, 2009;Perez-Ramirez et al, 2009), prior fasting (Chilibroste et al, 1997 and2007) and time of the day (Gregorini, 2012) on cow behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of effect on bite rate of time at pasture is in contrast to both Patterson et al (1998) and Chilibroste et al (1997) who, besides a negative relation between time at pasture and average bite rate, also found that the intensity declined during the day. Also Gibb et al (1998) found, that the bite rate was higher in the grazing period following morning milking compared with grazing later in the day, but it is interesting that time of day did not affect total jaw movements.…”
Section: Discussionmentioning
confidence: 40%
“…The size of the reduction in absolute intake and the increase in intake per hour at pasture in this experiment were higher than recorded for heifers grazing for a limited time (Ayantunde et al, 2001;Ginane and Petit, 2005) but lower than the results of Chilibroste et al (1997), who compared dairy cows grazing for periods varying from 1 h to 3 h 25 min after a period of 10 h without access to feed. The large effect found by Chilibroste et al (1997) might be an effect of a longer period of starvation and an even shorter time at pasture than in this experiment. Patterson et al (1998) showed that the intake of herbage increased, if the length of period before pasturing without access to feed was up to 6 h, while a longer period had no further effect on the intake of herbage in the following period at pasture.…”
Section: Discussionmentioning
confidence: 60%
“…The factors affecting intake rate in grazing cattle have been extensively studied, mainly on the short-term scale. In addition to factors related to sward structure such as sward height, herbage mass, bulk density and proportion of stem and pseudostem (McGilloway and Mayne, 1996;Prache and Peyraud, 1997), animal factors such as physiological state, animal nutritional requirements and fasting duration have been shown to affect intake rate at pasture (Chilibroste et al, 1997;Patterson et al, 1998;Gibb et al, 1999). However, little is known about the effect of restricting time at pasture on the performance, daily intake and feeding behaviour of dairy cows.…”
Section: Introductionmentioning
confidence: 99%